SISTEM PENUNJANG KEPUTUSAN UNTUK PEMILIHAN E-COMMERCE TERBAIK PADA PERUSAHAAN DIGITAL MARKETING MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS WEBSITE (Studi Kasus : PT. Lumbung Emas Astria) - rendy; Devi Yunita (Teknik Informatika Universitas Pamulang, 2025)
The development of information technology has significantly impacted the economic sector, particularly through the growth of e-commerce. PT. Lumbung Emas Astria (LEA Digital Agency), as a digital marketing agency, assists MSMEs in managing online stores across various platforms. However, challenges arise as each platform possesses different algorithms, often leading to ineffective marketing strategies and inefficient advertising costs. Currently, selecting the right platform is done conventionally. This study aims to develop a Web-based Decision Support System (DSS) to recommend the best e-commerce platform. The Simple Additive Weighting (SAW) method is employed to weigh criteria such as store performance, sales volume, communication features, and platform campaigns. Data collection was conducted through observation, interviews, and literature review. Based on system testing using sample data from 10 client stores, the application successfully identified Tokopedia as the best platform with the highest preference score of 8.68, followed by Shopee with 8.42, and TikTokshop with 7.37. Furthermore, functionality testing using the Blackbox Testing method demonstrated that the system is 100% valid and operates optimally. With this system, the LEA Digital Agency team can determine more efficient marketing strategies and help business owners minimize the risk of loss in the early stages of their business.